Exclusive Breastfeeding Practice and its Associated Factors among Mothers with Children Aged 6-23 Months in Dire Dawa, Eastern Ethiopia: A Community-based Cross-sectional Study - Assefa Desalew; Alekaw Sema; Yalelet Belay (Mashhad University of Medical Sciences, 2020)
Background & aim: Exclusive breastfeeding (EBF) is an essential need for the development and survival of the neonates, particularly in low-income countries. Therefore, the purpose of this survey was to determine the prevalence of EBF practice and its associated factors among mothers with children of 6-23 months in Dire Dawa Administration, eastern Ethiopia. Methods: This community-based cross-sectional survey was conducted on 704 participants in 15 kebeles in the Dire Dawa Administration using multistage sampling in 2018. The data were collected using a pretested interviewer-administered questionnaire. Binary logistic regression was used to identify the factors associated with EBF. Results: The magnitude of EBF practice was 81.1% (95% CI: 78.0-83.8). In the multivariate logistic analysis, the odds of EBF practice were signiﬁcantly higher among unemployed mothers (AOR: 1.93; 95% CI: 1.17-3.20), antenatal care (ANC) users (AOR: 1.69; 95% CI: 1.05-2.72), as well as the young mothers within the age ranges of 15-25 (AOR: 4.41; 95% CI: 1.90-10.20) and 26-35 (AOR: 2.16; 95% CI: 1.12-4.18) years. However, the subjects with bottle-feeding practice had lower odds (AOR: 0.55; 95% CI: 0.35-0.87), compared to those reported with EBF practice. Conclusion: The magnitude of EBF practice was almost as high as the recommended level. The unemployment status, ANC visit, maternal age, and bottle-feeding practice were the factors associated with EBF. Therefore, employed mothers should be provided with a special room in their workplace to breastfeed their children, daycare facilities, and/or six-month maternity leave. Also, healthcare workers should give attention to the encouragement of mothers to receive ANC.